Determination of 238U Content by Gamma Radiation Emitting from 234mPa Radionuclide - A. Khruschinski; S. Kutsen; A. Zhukouski; Naoyuki Sugai; Hiroshi Sugai; Michinori Mogi (Приборы и методы измерений, 2022)
Radionuclide 238U is one of the most important radioactive elements that must be controlled in nuclear power engineering, geological exploration, control of radioactive contamination of soils and raw materials used in construction. The most optimal way to control 238U is to use the 234mPa radionuclide, the activity of which, due to its short lifetime (≈ 1.2 min), is unambiguously related to the activity of 238U even if the secular equilibrium is disturbed in the sample under studyРossibility of use of the 234mPa nuclide gamma radiation to determine 238U with a scintillation detector in a medium containing natural radionuclides is investigated and demonstrated using the simplest examples. The proposed algorithm for determining of the 238U content is based on the Monte Carlo simulation of the detector response to the radiation of the 234mPa radionuclide at its 1001 keV energy line and subsequent processing of the experimental spectrum, including the Wiener filtering of the signal. This method makes it possible to determine the content of 238U in a continuous homogeneous medium while presence of natural radionuclides in it.The algorithm for determining of 238U content includes several main steps. Filtering based on the Wiener algorithm allows selecting a slowly changing part of the spectrum. Results of Monte Carlo simulations make it possible to determine the detection efficiency in a limited informative region of the spectrum, which includes, along with the 1001 keV peak from the 234mPa nuclide, which is a decay product of the radionuclide 234Th, and the peak of an interfering radionuclide from the decay chain of 232Th. This part of the spectrum does not contain any other lines of gamma radiation from natural radionuclides – decay products of both thorium and uranium chains. These two peaks in the spectral region under study can be separated from each other in a medium with a typical concentration of 234Th.Analysis of results of the activity of depleted uranium metal measuring in accordance with the proposed algorithm shows the possibility of determining of 238U content with an uncertainty of 3–5 %.